Vision-guided peg-in-hole assembly by Baxter robot - Yanjiang Huang; Xianmin Zhang; Xunman Chen; Jun Ota (Advances in Mechanical Engineering, 2017)
Dual-arm robot Baxter has been utilized in many applications. To use the Baxter robot realize a peg-in-hole assembly task, we proposed a step-by-step grasping strategy and a vision-guidance method for the Baxter robot. The step-by-step grasping strategy was used to position and grasp a peg and a hole on the working platform. At the assembling process, the positioning error was derived by the camera attached on the robot end-effector, and the positioning error was compensated through proportional–integral–derivative controller. Experiments were conducted to evaluate the grasping strategy and the vision-guidance method. Experimental results show that the Baxter robot can grasp the peg and the hole from the working platform, and the peg in hole with 1 mm clearance can be assembled successfully.